BENTUK TANGGUNGJAWAB NEGARA MENGHADAPI COVID-19 DALAM PERSEPKTIF OTONOMI DAERAH (Telaah Peraturan Pemerintah Nomor 21 Tahun 2020 tentang Pembatasan Sosial Berskala Besar) - Haqkidah Kancana; Dauri Dauri; Ummi Rahmatinnur; Nadya Waliyyatun Nisa; Retias Dewi J (SUPREMASI: Jurnal Pemikiran, Penelitian Ilmu-ilmu Sosial, Hukum dan Pengajarannya, 2020)
This study aims to look at the state's responsibility in protecting Indonesian citizens who have been affected or who have tested positive for co-19 in accordance with the 1945 Constitution and the health law and the policy of implementing Large Scale Social Restrictions (PSBB) for each region. The method used is Normative Juridical and Empirical Juridical, by examining documents and regulations and facts that occur in the community. The results of this study show that the responsibility of the state in dealing with COVID-19 is to protect its citizens by implementing PSBB which is considered to be able to reduce the transmission of the virus. In addition to providing medical aid assistance to food needs to the community so they can carry out daily life. The conclusion is the PSBB itself is one of the government's strategies in preventing the possibility of spreading the corona virus.